A Voice from the Uneasiness: Black Women in the Improvised-Music World mid-20th Century - Bose, Somparna (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
This paper shows blackness as a part of the modern identity-making that is a resultant of the dialogue(s) with the state and the subsequent paradigms related to this. These, altogether, makes their racial identity, which further yields to their ethnicity. After and around Harlem Renaissance, this identity-making can be studied through the vantage point of ethnomusicology, which opens the scope of dialogic communication with the state thereafter. While this identity-making happens, there is a shifting process of establishing a resistance against the state (from gross and blatant way of direct rebellion to a subtle and cultural way of protest through an emergency of musicality of a new taste.)